2020
DOI: 10.1063/1.5140447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal annealing on the optical and structural properties of (311)B and (001) GaAsBi/GaAs single quantum wells grown by MBE

Abstract: The effect of Furnace Annealing (FA) and Rapid Thermal annealing (RTA) on the structural and optical properties of GaAs1-xBix/GaAs single quantum wells (SQW) grown on (001) and (311)B substrates by molecular beam epitaxy (MBE) was investigated. The structural properties were investigated by high-resolution X-ray diffraction (HR-XRD) and Transmission Electron Microscopy (TEM). The Bi concentration profiles were determined by simulating the HR-XRD 2θ-ω scans using dynamical scattering theory to estimate the Bi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…As-annealing treatment eliminates defects and improves the electrical properties of carbon-doped InGaAsBi films and, meanwhile, drives more C onto group-III sites as donors, which increases the electron concentration and mobility. [18] A possible mechanism is that as-annealing treatment eliminates Bi-related defects, [28][29][30] drives more Bi onto group-V sites, and increases the number of activated carbon donors by forming C-Bi bonds around the Bi-related defects. [18] Besides, a self-compensation and the incorporation of the carbon atoms in interstitial sites may also be part of the reasons.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…As-annealing treatment eliminates defects and improves the electrical properties of carbon-doped InGaAsBi films and, meanwhile, drives more C onto group-III sites as donors, which increases the electron concentration and mobility. [18] A possible mechanism is that as-annealing treatment eliminates Bi-related defects, [28][29][30] drives more Bi onto group-V sites, and increases the number of activated carbon donors by forming C-Bi bonds around the Bi-related defects. [18] Besides, a self-compensation and the incorporation of the carbon atoms in interstitial sites may also be part of the reasons.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Dilute Bi compound semiconductors [ 1,2 ] have attracted much attention owing to their unique characteristics such as bandgap narrowing, [ 2–4 ] a temperature‐independent bandgap, [ 5 ] Auger effect suppression, [ 6 ] and improved crystal quality due to the surfactant effects of Bi. [ 7 ] The most commonly investigated dilute bismide system is GaAsBi, [ 8–18 ] and several research groups have demonstrated GaAsBi laser diodes. [ 19,20 ] Although there has been less research on dilute bismides in the InP system, [ 21–23 ] this system is important for longer‐wavelength applications such as fiber optic communications and infrared optics sensing.…”
Section: Introductionmentioning
confidence: 99%